Approaches in the Treatment of Cesarean Scar Pregnancy and Risk Factors for Intraoperative Hemorrhage: A Retrospective Study - Lin, Yaying; Xiong, Chang; Dong, Chunlin; Yu, Jinjin (Frontiers in Medicine, 2021)
Background: Cesarean scar pregnancy (CSP) involves a rare form of placental attachment that often leads to life-threatening conditions. The best treatment for CSP has been debated for decades. We aimed to evaluate the different treatments for CSP and analyzed the risk factors for intraoperative hemorrhage. Methods: CSP patients treated at the Affiliated Hospital of Jiangnan University were reviewed retrospectively from Jan 2014 to Jan 2020. CSP was classified into three types based on the location and shape of gestational tissue, blood flow features, and thickness of the myometrium at the incision site. The clinical characteristics, types, approaches of treatment, and clinical outcomes of CSP were analyzed. Results: A total of 55 patients were included in this study, 29 (52.7%) of whom underwent transvaginal curettage after uterine artery embolization (UAE); and 22 (40%) of whom underwent transabdominal ultrasound-guided hysteroscopic curettage (USHC) in type I and II. Four patients (7.3%) classified as type III underwent laparoscopic cesarean scar resection (LCSR). Intraoperative blood loss, blood transfusion rate, and scar diverticulum were significantly higher in type II than in type I (P < 0.05). Even though USHC showed no differences in intraoperative blood loss, length of stay, and scar diverticulum compared with curettage after UAE (P > 0.05), superiority was found in surgical time and hospitalization cost (P < 0.05). Furthermore, the type of CSP (OR 10.53, 95% CI: 1.69–65.57; P = 0.012) and diameter of the gestational sac (OR 25.76, 95% CI: 2.67–248.20; P = 0.005) were found to be risk factors for intraoperative hemorrhage. Conclusions: Transabdominal ultrasound-guided hysteroscopic curettage is an effective and relatively safe treatment option for patients with CSP. Type of CSP and diameter of the gestational sac were found to be associated with excessive intraoperative hemorrhage.